Unfolded Protein Response: A Regulator of the Endothelial Barrier - Nektarios Barabutis (Endocrine and Metabolic Science, 2021)
Recent evidence suggest that the endothelial barrier function is enhanced by the mild activation of the unfolded protein response (UPR), which aims to suppress abnormal increases of endoplasmic reticulum stress. Heat shock protein 90 inhibitors and growth hormone releasing hormone antagonists exert the capacity to activate this multifaceted cellular mechanism (UPR). Thus, investigations on the signalling network involved in those events, may deliver exciting opportunities in diseases related to endothelial barrier dysfunction. The diverse spectrum of those pathologies include sepsis and Acute Respiratory Distress Syndrome (ARDS).